Gene-Edited Interleukin CAR-T Cells Therapy in the Treatment of Malignancies: Present and Future - Zhang, Zhengchao; Miao, Lele; Ren, Zhijian; Tang, Futian; Li, Yumin (Frontiers in Immunology, 2021)
In recent years, chimeric antigen receptor T cells (CAR-T cells) have been faced with the problems of weak proliferation and poor persistence in the treatment of some malignancies. Researchers have been trying to perfect the function of CAR-T by genetically modifying its structure. In addition to the participation of T cell receptor (TCR) and costimulatory signals, immune cytokines also exert a decisive role in the activation and proliferation of T cells. Therefore, genetic engineering strategies were used to generate cytokines to enhance tumor killing function of CAR-T cells. When CAR-T cells are in contact with target tumor tissue, the proliferation ability and persistance of T cells can be improved by structurally or inductively releasing immunoregulatory molecules to the tumor region. There are a large number of CAR-T cells studies on gene-edited cytokines, and the most common cytokines involved are interleukins (IL-7, IL-12, IL-15, IL-18, IL-21, IL-23). Methods for the construction of gene-edited interleukin CAR-T cells include co-expression of single interleukin, two interleukin, interleukin combined with other cytokines, interleukin receptors, interleukin subunits, and fusion inverted cytokine receptors (ICR). Preclinical and clinical trials have yielded positive results, and many more are under way. By reading a large number of literatures, we summarized the functional characteristics of some members of the interleukin family related to tumor immunotherapy, and described the research status of gene-edited interleukin CAR-T cells in the treatment of malignant tumors. The objective is to explore the optimized strategy of gene edited interleukin-CAR-T cell function.